Modified thermal energy storage unit for solar cookers using iterative design algorithm. (2022) - Anilkumar, B.C.; Maniyeri, Ranjith; Anish, S.
Abstract: The use of phase change materials (PCMs) as thermal energy storage (TES) mediums has gained notable attention in recent years due to their high energy density and constant temperature characteristics which makes them suitable for solar cookers (SCs). Therefore, the primary objective of this study is to develop a modified TES unit containing PCM as heat storage medium incorporated with cooking vessel for SCs. The TES units use PCM filled on all sides, including the lid, enhancing heat transfer to food load. The design of TES unit is carried out by developing computational procedure. MATLAB code is written to implement the iterative procedure, simplifying exhaustive calculations required for optimizing and designing the TES unit. The present work also aims to design, fabricate and test different geometries of TES units using paraffin wax as the PCM. After six hours, cooking load temperature in all geometries of TES units reached the melting point of PCM. TES units with cylindrical shapes perform best among hexagon and square designs. Through computational procedure, cylindrical configuration is the best as it takes least amount of PCM to keep steady temperature over a specific period. Based on the computational procedure developed in this study, TES container will be designed to enhance SC performance during sundown hours and maximize the use of latent heat stored within the PCM.